2013
DOI: 10.1073/pnas.1310067110
|View full text |Cite
|
Sign up to set email alerts
|

RARα-PLZF oncogene inhibits C/EBPα function in myeloid cells

Abstract: In acute promyelocytic leukemia, granulocytic differentiation is arrested at the promyelocyte stage. The variant t(11;17) translocation produces two fusion proteins, promyelocytic leukemia zinc finger-retinoic acid receptor α (PLZF-RARα) and RARα-PLZF, both of which participate in leukemia development. Here we provide evidence that the activity of CCAAT/enhancer binding protein α (C/EBPα), a master regulator of granulocytic differentiation, is severely impaired in leukemic promyelocytes with the t(11;17) trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Furthermore, HDACs are critical for the optimal oncogenic activity of leukemia fusion proteins. For example, AML1-ETO, PML-RARα and RARα-PLZF cause transcriptional repression of genes responsible for hematopoietic differentiation via recruitment of HDAC1/3, thus contributing substantially to leukemogenesis [99][100][101][102][103][104][105][106][107]. Given that the expression and activity of HDACs are closely related to the etiology of hematological malignancies, HDACs are hot targets for clinical drug development.…”
Section: The Clinical Implications Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…Furthermore, HDACs are critical for the optimal oncogenic activity of leukemia fusion proteins. For example, AML1-ETO, PML-RARα and RARα-PLZF cause transcriptional repression of genes responsible for hematopoietic differentiation via recruitment of HDAC1/3, thus contributing substantially to leukemogenesis [99][100][101][102][103][104][105][106][107]. Given that the expression and activity of HDACs are closely related to the etiology of hematological malignancies, HDACs are hot targets for clinical drug development.…”
Section: The Clinical Implications Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…31 Besides, the function of CEBPα in cell proliferation arrest and tumor suppression had been extensively studied. [32][33][34] Here we found that more CEBPα mRNAs (Supplementary Figure 3D) and proteins ( Figure 3a) were found in lincRNA-uc002yug.2-low cells. And, a significant negative correlation (R 2 = 0.162, P = 0.046) between the transcriptional levels of RUNX1a and CEBPα was found, whereas a significant negative correlation (R 2 = 0.246, P = 0.013) existed between the transcriptional levels of lincRNA-uc002yug.2 and CEBPα (Figure 3b).…”
Section: Runx1 Affects Cebpα Gene Expression Via Conserved Promoter Amentioning
confidence: 56%
“…Molecular studies reveal that the PLZF/RARA fusion protein acts mainly as an epigenetic regulator of its target genes by directly interacting with the Polycomb protein Bmi‐1 to recruit PRC1 to the retinoic acid response elements . On the other hand, RARA/PLZF recruits HDAC1 to cause histone H3 deacetylation at the C/EBPα locus, leading to a decrease in the expression of C/EBPα target genes, and thus inhibiting myeloid differentiation to promote self‐renewal of myeloid progenitors .…”
Section: Stem Cell Self‐renewalmentioning
confidence: 99%